The value of a digital management system for the medical records of patients with cerebral hemorrhage - Qin Zhang; Xiao-Dong Li (Frontiers in Public Health, 2023)
ObjectiveThe present study aimed to explore the value of a digital management system based on micro digital imaging technology for the medical records of patients with cerebral hemorrhage.MethodsA total of 540 patients with intracerebral hemorrhage diagnosed and treated in the hospital from November 2016 to November 2019 were selected as the subjects of this study. A digital management system based on micro digital imaging technology was used to establish how to handle the medical records of these patients.ResultsThe medical record management process of patients with cerebral hemorrhage comprises five modules: medical record editing, medical record querying, medical record borrowing management, statistical analysis, and system maintenance. The purpose of these is to manage and store digitalised medical records for patients, present the most useful information on the first page of the medical records, monitor the safety of the medical records, and enable real-time data sharing.ConclusionEstablishing a digital management system based on micro digital imaging technology for the medical records of patients with cerebral hemorrhage can effectively enable the preservation and use of these documents. It improves information management, such as data sharing, security, and the overall level of information. This is worth promoting.